"FOSTERING ADVANCED PROFESSIONAL COMMUNICATIVE COMPETENCE IN UNIVERSITY STUDENTS VIA INNOVATIVE TECHNOLOGIES IN THE COURSE 'CULTURE OF SPEECH AND COMMUNICATION'" - Musayeva , Amina (Центральноазиатский журнал междисциплинарных исследований и исследований в области управления, 2024)
This study explores the cultivation of advanced professional communicative competence among university students through the integration of innovative technologies in the "Culture of Speech and Communication" course. Utilizing a multifaceted approach, incorporating cutting-edge technological tools, the research aims to assess the impact of these innovations on students' communicative proficiency. The investigation delves into the effectiveness of technology-enhanced learning in fostering nuanced speech and communication skills essential for professional success. Through a comprehensive analysis of the outcomes, this study contributes valuable insights to the evolving landscape of technology integration in higher education and its role in shaping communicative competence.